2021
DOI: 10.1142/s0192415x21500555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulating Local and Distal Acupoints on Diabetic Gastroparesis: A New Insight in Revealing Acupuncture Therapeutics

Abstract: One of the most important aspects of clinical acupuncture practice, like diabetic gastroparesis, is the selection of suitable acupoints. Furthermore, it is critical to examine the therapeutic impact differences between distal and local acupoints, as well as the prescription of their combination. In this study, diabetic gastroparesis rats were treated by needling Zhongwan (CV12) and Zusanli (ST36), and then used Single Photon Emission Computed Tomography-CT (SPECT-CT) technology to assess the effects of promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Selection of acupoints is one of the determinative factors influencing acupuncture effect, as it is the first step and foundation of acupuncture operation [ 16 , 17 ]. In the current clinical practice, the composition of acupoint prescriptions is mainly based on acupuncturists’ clinical experience, and the choice of acupoints varies depending on the acupuncturists’ practice style [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selection of acupoints is one of the determinative factors influencing acupuncture effect, as it is the first step and foundation of acupuncture operation [ 16 , 17 ]. In the current clinical practice, the composition of acupoint prescriptions is mainly based on acupuncturists’ clinical experience, and the choice of acupoints varies depending on the acupuncturists’ practice style [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence showed acupuncture has a positive impact on the earlier return of GI function when compared with those receiving a control treatment. Certain studies have supported that EA at ST36, ST37, ST39, or CV4 protected SMC to improve gastrointestinal transit by reducing local inflammation in the intestinal musculature [44] ; acupuncture can promote the secretion of motilin, change the activity the intestinal nervous system, [45,46] and effectively relieved systemic inflammation by restraining local intestinal inflammatory response. [47] The results also showed that acupuncture was beneficial for postoperative nausea and vomiting, and it had a better effect on the less severe symptoms.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…Since local acupoints and distal acupoints may belong to different meridians, synergic effects can be achieved by using them together. [ 15 ] Acupoint selection can be divided into local acupoint selection, distal acupoint selection and empirical acupoint selection. Proximal acupoint selection is to select similar acupoints for treatment according to the location of the disease, distal acupoint selection is to select the far meridians and collaterals related to the disease, and experiential acupoints are acupuncture points that have special therapeutic effects for a certain disease.…”
Section: Discussionmentioning
confidence: 99%